Stakeholder collaboration for solid waste management in a small tourism island - Jarotwan Koiwanit; Viachaslau Filimonau (PLoS ONE, 2023)
Although stakeholder collaboration is key for sustainable development of tourism in small islands, research on its determinants is only emerging. The lack of empirical studies hampers an understanding of how effective stakeholder partnerships for sustainability in small tourism islands can be formed and sustained. To partially address this knowledge gap, this study explores stakeholder collaboration for solid waste management in the island of Koh Phayam, Thailand, from the perspective of stakeholder theory, social capital and proximity effect. Semi-structured interviews (n = 26) reveal a lack of understanding of collaboration benefits alongside leadership and reciprocity among stakeholders. However, due to geographical proximity, the level of stakeholder trust in each other is significant, thus indicating potential for future successful partnerships. For these partnerships to become effective, a system of financial incentives for stakeholders to separate and recycle solid waste in situ should be designed. To improve stakeholder communication and reciprocity, capacity building workshops and round tables can be organised. Municipal authorities should lead on solid waste management, and a steering committee comprising the representatives of all other stakeholders needs to be established to oversee the work of municipal authorities. Lastly, the feasibility of setting private public partnerships for solid waste management in Koh Phayam should be considered given the significant extent of knowledge and trust among local stakeholders. External stakeholders, such as farmers, can be involved in management of organic waste, thus extending the scope of partnerships for sustainability beyond the island.
Keywords: Diverse Aspects of Tourism Research; Religious Tourism and Spaces; Municipal Solid Waste Management